Consumer Segmentation Based on Food-Related Lifestyles and Perception of Chicken Breast - Ripoll , G.; Alberti, P.; Panea, B. (International Journal of Poultry Science, 2015)
The aim of this study was to disseminate knowledge regarding the perceptions of Spanish consumers of chicken breast and their related lifestyles and to classify different consumer groups according to their food-related lifestyles. Nearly all Spanish consumers consume chicken breast once or twice per week. The preference for white or yellow chicken appears to be divided evenly, although the preferred is white chicken. Chicken breast is perceived as a product of convenience. Seventy percent of consumers buy chicken breast because it is easy to cook whereas only 27% prefer to buy the entire chicken. Four groups of consumers based on their lifestyles and their perceptions of chicken breast were identified: "Urban single", "Traditional", "Innovative precariat" and "Gourmet". These types of consumers are consistent with types other studies have identified in terms of the lifestyles associated with other foods. Defining groups of consumers with differentiated perceptions of chicken breast is useful in managing marketing strategies to satisfy the various consumption needs associated with chicken breast.